Pelatihan Pembuatan Es Krim Buah Naga Sebagai Upaya Peningkatan Gizi Keluarga bagi Kader PKK Kadipiro Banjarsari Surakarta - Reslely Harjanti; Siti Aisiyah; Vivin Nopiyanti; Titik Sunarni; Suhartinah Suhartinah (Universitas Islam Nahdlatul Ulama Jepara, 2020)
The community and especially children really like snacks such as ice cream. The use of dragon fruit as a component in ice cream is expected to be able to make people enjoy the sweetness and also get the intake of anthocyanins, especially those with antioxidant properties. The purpose of this activity is to provide skills training in the use of dragon fruit as the main component for ice cream making to PKK members in Kadipiro sub-district, Banjarsari District, Surakarta. The service activity begins with an explanation of the usefulness of dragon fruit and its phytochemical content. After that it was continued with training in making ice cream to PKK members. The training activities were divided into several stages starting from the tutorial then continued with mentoring from the team and ended with an evaluation of the implementation of the activities. The results from this activity are 1) participants have the understanding about nutrition of dragon fruit; 2) They understand procedure to make home made dragon fruit ice cream; 3) they able to make ice cream by themselves